Položaj študija dela v gozdarstvu Slovenije in primerjave s tujino - Košir, Boštjan (Gozdarski vestnik, 2016)
We deal with the current situation of work study in the forestry and we refer to the analysis of the local situation in the forestry at the expiration of concession relations. We include the results of the international work study comprising all continents which also answered to the questions, how the work study is viewed in an individual region. Separately we deal with results from Europe. In the last part we emphasize the tasks of work study, which are of public character and do not concern explicitly business and organizational aspects.
Keywords: forestry; gozdarstvo; študij dela; anketa; učinki; stroški; javni značaj